Effects of Flower-Enriched Ecological Focus Areas on Functional Diversity Across Scales - Nilsson, Lovisa; Klatt, Björn K.; Smith, Henrik G. (Frontiers in Ecology and Evolution, 2021)
Ecological Focus Areas (EFAs) to benefit biodiversity became mandatory in intensively farmed landscapes after the reform of the European Common Agricultural Policy (CAP) in 2013. The implementation of EFAs as uncropped field margins has been criticized as ineffective but created a window of opportunity to test if augmenting them with annual flower strips can benefit biodiversity. In this study, we investigated if annual flower strips on EFAs benefitted functional biodiversity in intensively farmed landscapes. To this end we established eleven annual flower strips with a seed mixture targeted for both natural enemies and pollinators, on areas were farmers had planned for EFAs. We determined effects on aphids and their natural enemies in cereal fields close to six of the flower strips, and for solitary bees and wasp close to and in the surroundings of all eleven flower strips. We found that annual flower strips benefitted the abundance of hoverfly larvae and possibly also that of solitary bees. However, there were neither any significant effects on natural enemies (other than hoverfly larvae), nor any difference in natural pest control as shown by lack of differences in aphid numbers and parasitation rates. Abundances of solitary bees and wasps in the surrounding landscapes were unaffected, although there was a tendency for more solitary bee cells closer to the strips. We suggest that the critical issue leading to the mostly negative results is the lack of permanent structures to sustain populations of arthropods that in turn can benefit from annual flower strips. Hence, future agri-environmental policies need to carefully consider if and how annual agri-environmental measures should be implemented in intensively managed agricultural landscapes, e.g. by combining them with more permanent structures.